The Effect of Subchronic Administration of Soursop (Annona muricata) Leaf Aqueous Extract In Bax Expression on Gastric Glandular and Non Glandular Mucosal Epithelium of Rat (Rattus norvegicus) - Ety Sari Handayani; Zainuri Sabta Nugraha; Chandra Muhammad Rauf; Yusa Muhammad Thoriq; Nurul Hidayah (EKSAKTA: Journal of Sciences and Data Analysis, 2022)
Soursop leaf water extract (SLWE) contains acetogenin compounds which are mitochondrial complex I inhibitors. This compound can reduce cellular ATP production and induce apoptosis via bax pathways, causing side effects on cells. Gaster is a digestive organ that has direct contact with acetogenin. Gastric cells contain mitochondria and undergo physiological apoptosis.This study aims to determine the effect of subchronic administration of SLWE on bax expression on glandular/non glandular mucosal epithelium gastric of rats. This study was conducted at Research Laboratorium, Medical Faculty, UII, 2019. This study uses post test only control group design. The subjects were 10 female rats, Spraque-dawley strain which was divided into 2 groups; the treatment and the control group. The treatment group received extract of SLWE at a dose of 1000 mg/kgBB/day for 30 days, while the control group received aquades, both were administered using sonde. Observation of bax expression was performed on each IHC preparation with bax antibody. The difference in bax expression between the control and treatment groups was tested by t-test. There were significant differences in the number of bax expressions in gastric glandular mucosa (p 0.038) and non-glandular gastric mucosa (p 0.027) between the treatment group and the control group. There was an effect of subchronic administration of SLWE on bax expression on mucosalepithelium for both, glandular and non-glandular of rat gaster. There were differences in the number of glandular gastric as well as non-glandular gastric mucosa epithelium which exerted bax between the control and treatment groups